Design and Implementation of Data Mining Tools - Thuraisingham, Bhavani; Khan, Latifur; Awad, Mamoun; Wang, Lei (Auerbach Publications, 2009)
Based on the authors' own research work, this book explains how to create and employ systems and tools for intrusion detection, Web page surfing prediction, and image classification. Focusing on three applications of data mining, the book takes a practical approach to the subject. A hands-on guide, it discusses the performance results, limitations, and unique contributions of data mining systems. It provides essential information for technologists to decide on the tools to select for a particular application, for developers to focus on alternative designs if an approach is unsuitable, and for managers to choose whether to proceed with a data mining project.